Identification and characterisation of maize microRNAs involved in developing ears. (14th May 2013) - Ding, D.; Li, W.; Han, M.; Wang, Y.; Fu, Z.; Wang, B.; Tang, J.; Mendel, R.
Abstract In maize, kernel row number trait is determined during the period when spikelet pair meristems (SPMs) give rise to spikelet meristems (SMs). Expression levels of many genes change during this period due to regulation at transcriptional and post‐transcriptional levels. MicroRNAs (miRNAs) act as key regulating factors of post‐transcriptional gene expression. To discover miRNAs involved in maize ear development, Solexa deep sequencing was performed on a maize inbred line, Zong3. Ears at the stage when SPMs produce SMs were harvested to extract RNA. Deep sequencing revealed 85 conserved miRNAs belonging to 17 miRNA families. miRNA families differed greatly in their abundance, from over 160, 000 to only five reads. In addition, 31 novel maize miRNAs were identified using stringent criteria. The results show that miRNA‐mediated regulation of gene expression is present in developing maize ears at the stage when SPMs produce SMs; both conserved and novel miRNAs are involved.